Low-velocity impact characterization of fiber-reinforced composites with hygrothermal effect - Zai, Behzad Ahmed; Khan, Muhammad; Park, M. K.; Shahzad, Majid; Shahzad, M. A.; Salman, Nisar; Khan, Sohaib Zia; Khan, Kamran Ahmed; Shah, Aqueel (ASTM International, 2018)
In this article, low-velocity impact characteristics of UHN125C carbon fiber/epoxy composite, including unidirectional (0°), cross-directional (0°/90°), and quasi-isotropic layups, were experimentally measured. The effect of the fiber orientation angle and stacking sequences on impact force and induced strain were measured via an instrumented drop-weight apparatus with special concern for the moisture absorption effect. Dried specimens were immersed in distilled water for a certain period of time to absorb water for intermediate and saturated moisture content. It was observed that the impulse was reduced with the increase in moisture content; on the other hand, strain increased with moisture, as measured by DBU-120A strain-indicating software (MADSER Corp., El Paso, TX). Impact damage is widely recognized as one of the most detrimental damage forms in composite laminates because it dissipates the incident energy by a combination of matrix damage, fiber fracture, and fiber-matrix debonding. Therefore, it is extremely important to know the impact strength of a structure, especially for applications in industries such as aerospace, ship design, and some other commercial applications. The use of composite materials in engineering applications is increasing rapidly because they have higher strength-to-weight ratios than metals. The strength, stiffness, and, eventually, the life of composite materials are affected more than conventional materials by the presence of moisture and temperature. Thus, it is necessary to analyze the response of composites in a hydrothermal environment.
Keywords: Dynamic strain; Fiber orientation; Moisture content; Impulse; Layup